Nutritional composition and biochemical characteristics of five date palm fruit (Phoenix dactylifera L.) varieties at the Khalal stage grown in Kuwait - Maryam Al-Hilal; Zeinab Moussa; Alfred Anderson (Kuwait Journal of Science)
Palm dates are among the most highly cultivated and consumed fruits in Kuwait and other Arabian Gulf countries. However, data on the nutritional content of Kuwaiti date fruits remain scarce. This study investigated the biochemical and nutritional composition of five cultivars of Kuwaiti fresh date fruits to determine the health value of Kuwaiti dates. Samples of cultivars grown in Kuwait were analyzed for energy, protein, carbohydrates, sugars, antioxidants, and micro-minerals. Varieties studied had high energy values ranging between 351.63 kcal/100g and 368.35 kcal/100g. They were rich in potassium (4450-7128mg/100g), with significant amounts of calcium (287.8-469.1mg/100g), magnesium (130.3 -294.5 mg/100g), sodium (70.7-123.3 mg/100g), iron (2.45-3.2 mg/100g) and manganese (0.7-1.55 mg/100g). Gallic (19.97-5.47 mg/100g), chlorogenic (0-0.712mg/100 g), and ascorbic (0.624-0.875 mg/1mg) acids were the main antioxidants. The data indicate that the Kuwaiti date fruit is a rich source of essential nutrients making it an important local product that requires further investigations for its nutritional properties and industrial utilization prospects.